The use of ICTs and other social media, and their effectiveness in disseminating health-related information about chronic illness - Teddy, anak Edwin Chapun. (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study was carried out in order to understand about the use of ICTs and other social media, and their effectiveness in disseminating health-related information about chronic illness among the serian community in Sarawak.